The readable people of George Meredith - Wilt, Judith, 1941- (Princeton University Press, 1975)
Meredith's reputation as an ""unreadable"" novelist prompted Judith Wilt to examine the relationship between author and reader in Meredith's fiction-a relationship that was combative and teacherly and, she contends, a central aspect of his art. Meredith was concerned with ""readable people, "" by whom he meant his readers (as he imagined them and as they were), his characters (as he created them and as they were perceived), and himself. Focusing on Meredith's struggle to shape and change the reader, Judith Wilt examines five novels: The Ordeal of Richard Feverel, Sandra Belloni, The Egoist, On.
Includes index.
Keywords: Meredith, George, -- 1828-1909 -- Criticism and interpretation.; Meredith, George, -- 1828-1909 -- Critique et interpretation.; Meredith, George, -- 1828-1909; Psychological fiction, English -- History and criticism.; Characters and characteristics in literature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Characters and characteristics in literature; Psychological fiction, English; Criticism, interpretation, etc.